2019
DOI: 10.1002/fsn3.1270
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, nutritional, and quality parameters of salted semidried mullet (Chelon haematocheilus) prepared with different processing methods

Abstract: The mullet (Chelon haematocheilus) is a cosmopolitan coastal species. It is often consumed as a sliced raw fish in Korea and as a dried and salted fish roe in several countries, including the southeastern United States and Japan. In this study, to optimize traditional processing of salted semidried mullet (SSDM) for the development of high‐quality products, nine different types of traditional process were applied, and quality changes including physicochemical, nutritional, and sanitary properties were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Changes in the PV, AV, and TBARS values of the FM and SSDM groups during 21 days storage in the refrigerator at 4 °C are shown in Figure 3 . PV is an indicator of primary lipid oxidation and malodor formation [ 12 ]. The experimental results indicated that the initial PV of the FM and SSDM groups was low (1.33–2.1 mEq/kg), indicating the good quality of the product in terms of lipid oxidation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in the PV, AV, and TBARS values of the FM and SSDM groups during 21 days storage in the refrigerator at 4 °C are shown in Figure 3 . PV is an indicator of primary lipid oxidation and malodor formation [ 12 ]. The experimental results indicated that the initial PV of the FM and SSDM groups was low (1.33–2.1 mEq/kg), indicating the good quality of the product in terms of lipid oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Protein levels of around 60–70% are present in the muscle fibers of fish meat [ 12 ]. The protein patterns in the FM and SSDM experiments were analyzed using SDS-PAGE electrophoresis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This issue has also been raised about salted dried fish. According to findings by Jo et al [8], the approximated compositions of salted semi-dried mullet (SSDM) are moisture (66.1-71.8), ash (1.65-3.75%), crude protein (16.12-18.09%) and crude lipid (1.11-2.07%). These results have been proven to be achieved by the different processing techniques, such as salt concentration and drying methods, affecting salinity, water activity (Aw), colour parameters, peroxide value (POV), acid value (AV), thiobarbituric acid (TBA), and total volatile basic nitrogen (TVB-N) contents in fresh mullet (FM) and different SSDM groups.…”
Section: Nutritive Valuementioning
confidence: 99%